2018
DOI: 10.5114/ceh.2018.80125
|View full text |Cite
|
Sign up to set email alerts
|

Predictive power of Model for End-Stage Liver Disease and Child-Turcotte-Pugh score for mortality in cirrhotic patients

Abstract: Aim of the studyTo assess the performance of Child-Turcotte-Pugh (CTP) and Model for End-Stage Liver Disease (MELD) scores’ kinetics during hospitalization in predicting in-hospital mortality in patients with liver cirrhosis.Material and methodsOne hundred and seventy-four cases of hospitalized liver cirrhosis patients were selected. The diagnosis of cirrhosis was made based on clinical, biochemical, ultrasonic, histological, and endoscopic findings and results. CTP and MELD scores at admission and ΔCTP and ΔM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Another important finding is significant improvements in liver function and liver enzymes. Child–Pugh is considered a strong bedside prognostic indicator in advanced liver disease, often used with MELD to determine need and priority for transplant [ 18 ]. Here, the vast majority improved both scores or remained steady, which correlates with an increase in serum albumin, another clinical prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important finding is significant improvements in liver function and liver enzymes. Child–Pugh is considered a strong bedside prognostic indicator in advanced liver disease, often used with MELD to determine need and priority for transplant [ 18 ]. Here, the vast majority improved both scores or remained steady, which correlates with an increase in serum albumin, another clinical prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…All patients filled out the Euro-Qol Index survey, including the visual analog scale evaluation at baseline and at 12 m. We also incorporated the nonutility-based Short Form-36v2 survey, which provides a detailed profile of health-related quality of life [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, malnutrition emerged as a robust predictor of pre‐transplant mortality in the majority of studies, an association with death found in 69% of evaluated NAT data points, with a RR for mortality ranging from 2.2 to 5.8. This evidence that 7 out of 10 times that it was evaluated, malnutrition was associated with pre‐transplant mortality, adds data to support the use of malnutrition as a potentially modifiable prognostic factor in patients with cirrhosis . The association of malnutrition with post‐transplant mortality was less clear, identified in only 28% of evaluated NAT data points, with a RR of death of 3.0 from the meta‐analysis.…”
Section: Discussionmentioning
confidence: 79%
“…This evidence that 7 out of 10 times that it was evaluated, malnutrition was associated with pre-transplant mortality, adds data to support the use of malnutrition as a potentially modifiable prognostic factor in patients with cirrhosis. 67 The association of malnutrition with post-transplant mortality was less clear, identified in only 28% of evaluated NAT data points, with a RR of death of 3.0 from the meta-analysis. Given the small number of studies evaluating non-mortality outcomes, it is challenging to draw definitive conclusions for the association of malnutrition with these measures.…”
Section: Pre Hoc Sensitivity Analysesmentioning
confidence: 92%
“…The patients' clinical and laboratory data were collected: (1) the 12-week survival rate; (2) the Child-Turcotte Pugh (CTP) score [21] and model for endstage liver disease (MELD) score [22] before and after treatment for 4, 8, and 12 weeks; (3) biochemical indicator: serum ALT, AST, total bilirubin (TBIL), and albumin (ALB) at 0, 4, 8, and 12 weeks after treatment, respectively; all assays used a colorimetric method (Automatic Analyzer 7170A, Hitachi, Japan); (4) PTA was performed following the manufacturer's instructions (STA-evolution, STAGO, France). It was tested at 0, 4, 8, and 12 weeks after treatment, respectively.…”
Section: Methodsmentioning
confidence: 99%